1999
DOI: 10.1046/j.1525-1381.1999.09115.x
|View full text |Cite
|
Sign up to set email alerts
|

A Double‐Blind, Placebo‐Controlled, Randomized Trial of Cladribine in Relpaasing‐Remitting Multiple Sclerosis

Abstract: We conducted an 18-month, placebo-controlled, double-blind study to evaluate cladribine in the treatment of 52 patients with relapsing-remitting multiple sclerosis. Patients received either placebo or cladribine 0.07 mg/kg/day by subcutaneous injection for 5 consecutive days as six monthly courses for a total cumulative dose of 2.1 mg/kg. Analysis of results revealed a statistically significant favorable effect of cladribine on the joint frequency and severity of relapses and magnetic resonance imaging (MRI) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
102
0
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(106 citation statements)
references
References 23 publications
1
102
0
3
Order By: Relevance
“…There was also a significant reduction in the occurrence of Gd-enhancing lesions at 12 months compared with placebo (P = 0.0001), which remained significant lower at 18 months (P = 0.002). 27 Patients with primary or secondary progressive forms of MS, received parenteral cladribine in the 12-month MS-001 and 24-month treatment crossover MS-Scripps studies. 25 In the MS-001 study cladribine led to a .90% reduction in the mean number of T1 Gd-enhancing lesions at 6 months which was maintained throughout the study (P # 0.005 for the 0.7 mg/kg group and P = 0.001 for the 2.1 mg/kg group, versus placebo at final evaluation) and a .90% reduction in mean volume of T1 Gd-enhancing lesions in both cladribine groups after 6 months, which was also maintained throughout the study (P , 0.001 after 18 months and P = 0.007 after 24 months vs placebo).…”
Section: Clinical Efficacy and Safety Profile Of Cladribine In Ms CLImentioning
confidence: 99%
See 1 more Smart Citation
“…There was also a significant reduction in the occurrence of Gd-enhancing lesions at 12 months compared with placebo (P = 0.0001), which remained significant lower at 18 months (P = 0.002). 27 Patients with primary or secondary progressive forms of MS, received parenteral cladribine in the 12-month MS-001 and 24-month treatment crossover MS-Scripps studies. 25 In the MS-001 study cladribine led to a .90% reduction in the mean number of T1 Gd-enhancing lesions at 6 months which was maintained throughout the study (P # 0.005 for the 0.7 mg/kg group and P = 0.001 for the 2.1 mg/kg group, versus placebo at final evaluation) and a .90% reduction in mean volume of T1 Gd-enhancing lesions in both cladribine groups after 6 months, which was also maintained throughout the study (P , 0.001 after 18 months and P = 0.007 after 24 months vs placebo).…”
Section: Clinical Efficacy and Safety Profile Of Cladribine In Ms CLImentioning
confidence: 99%
“…Cladribine was generally well-tolerated in the individual Scripps studies in MS. 29,30 In a pooled analysis of the data with cladribine vs placebo from the three Scripps studies and an additional supportive study in patients with MS, the most commonly reported treatment-emergent AEs were upper respiratory tract infections (32 vs 24%), headaches (28 vs 38%) and injection-site reactions (24 vs 25%). 27 There was a small dose-related increase in the frequency of upper respiratory tract and urinary tract infections (UTIs). AEs reported more often with cladribine than placebo treatment were hypertonia; purpura, muscle weakness and upper respiratory tract infections.…”
Section: Safety and Tolerabilitymentioning
confidence: 99%
“…Smaller placebo-controlled trials of subcutaneously administered cladribine in chronic progressive and relapsing-remitting MS revealed promising results, not only clinically but also in MRI parameters. [72][73][74] However, a double-blind, placebo-controlled phase III study of subcutaneously administered cladribine in 159 patients with secondary and primary progressive MS unexpectedly failed to exhibit significant clinical and MRI benefits after one year. 75 As cladribine also exists in an oral formulation and as pilot trials also have provided encouraging data, 76 a large randomized, double-blind, placebocontrolled phase III trial, including 1,290 patients with active inflammatory relapsing-remitting MS has recently been initiated.…”
Section: Cladribinementioning
confidence: 99%
“…These patients did not receive medications for at least 3 months prior to the study and comprised a placebo group enrolled in a previous study (Romine et al, 1999). The studies reported here were approved by the Human Subjects Committee of Scripps Clinic, Scripps Green Hospital and The Scripps Research Institute (TSRI).…”
Section: Patientsmentioning
confidence: 99%
“…MRI was performed using a 1.5-T General Electric Signa scanner (Romine et al, 1999). T2 and proton density-weighted images were obtained by conventional spin-echo sequence with repetition times of 2500 ms and echo delay of 30 and 90 ms. Axial scans of 3-mm thickness and without interslice gap were obtained about 10 min after gadopentetate dimeglumine (GD) injection to assure optimal time for transmigration of the contrast agent across the blood-brain barrier.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%